Leveraging Social Media Data for Forest Fires Sentiment Classification: A Data-Driven Method - Warih Maharani; Hanita Daud; Noryanti Muhammad; Evizal Abdul Kadir (Journal of Information Systems Engineering and Business Intelligence)
Background: The rise in forest fires over the last two years, which is due to rise in dry weather conditions and human activities, have greatly impacted an area of 1.6 million hectares, leading to significant ecological, economic, and health issues, hence the need to improve disaster response strategies. Previous research determined the lack of coverage regarding public response during forest fires with conventional methods such as satellite images and sensor data. However, social media platforms provide real-time information generated by users, along with location information of disaster events. Sentiment analysis helps in understanding the public reactions and responses to natural disasters, thereby increasing awareness about forest fires.